Changer la réalité : les mods des jeux vidéo, la (micro)politique et les genres de l’imaginaire - Paweł Frelik (ReS Futurae)
The article examines the changing realities of video game mods, micro politics, and the fantastic. It argues for an intimate connection between the practice of modding and the genres of sf and fantasy. It first offers a brief introduction to the phenomenon of modding and sketches out its definition and contexts. It then mentions several fantastic mods and proposes critical frameworks within which they can be discussed. Finally, it problematizes the cultural presence of mods by tracing links between the fan modding practice on the one hand and the video game industry processes and dominant ideologies on the other.